OCA optical film and preparation method thereof
By adopting a five-layer structure OCA optical film, the combination of a modified silicon-containing adhesive layer and a modified PET matrix is solved, and the problem of poor heat resistance of traditional OCA adhesives is achieved, and a higher light transmittance is achieved , flame retardant properties and high temperature resistance.
Patent Information
- Application Number
- CN202411931509.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The poor heat resistance of traditional OCA adhesives leads to yellowing problems in film materials, limiting the application of OCA, and the prior art has failed to effectively solve this problem.
OCA optical film adopting a five-layer structure, including a fluorine-containing special-shaped film layer, a silicon-containing adhesive layer, a modified PET matrix, a silicon-containing adhesive layer and a fluorine-containing special-shaped film layer, by modifying the silicon-containing adhesive layer Combination with modified PET matrix improves the light transmittance and adhesion of the adhesive.
The OCA optical film has achieved excellent aging resistance, high temperature resistance and flexibility, and has better light transmittance, transmittance, flame retardant performance and low refractive index.
Smart Images

Figure BDA0005210436440000021 
Figure BDA0005210436440000041 
Figure BDA0005210436440000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical films, and in particular to an OCA optical film and a preparation method thereof. Background Art
[0002] With the continuous development of science and technology, there are more and more large electronic devices such as smart phones, tablets, smart TVs, etc. The screen is one of the most important components in this type of electronic products. The vast majority of screens are made of multiple layer structures such as display components, touch films, polarizers, cover plates, etc. These components need to be bonded together, so some adhesives are needed. Among them, OCA glue is one of the more common adhesives used in the field of flexible screens. At the same time, it also has broad application prospects in aerospace, transportation and other fields.
[0003] Traditional OCA is mainly based on acrylic acid system and polyurethane system, especially acrylic acid and urea system, which are widely used due to their good transparency, easy to involve and low price. However, the adhesion of traditional OCA glue is poor, so it needs to be improved.
[0004] For example, CN116200140A discloses "an OCA glue, an OCA layer, an OCA film and applications" which are prepared by using acrylate monomer A, acrylate monomer B, hydrophilic acrylate monomer, curing agent, tackifier, elastic resin, organic solvent and the like as main raw materials. The OCA layer has good adhesion and creep recovery properties and is not prone to cracks, deformation and the like.
[0005] For example, CN107353854B discloses "an OCA optical adhesive and an OCA optical adhesive film" which are prepared from saturated polyacrylate containing cross-linkable groups, oligomers containing unsaturated bonds, diluents, photoinitiators, and cross-linking agents. The optical film has high viscosity and good peelability.
[0006] However, in addition to the above-mentioned problems, the traditional OCA has poor heat resistance. The poor heat resistance will further cause the film material to turn yellow, limiting the application of OCA. The above-mentioned patent also does not mention and solve this problem.
[0007] Therefore, it is urgent to develop an OCA optical film that is resistant to yellowing due to aging, resistant to high temperatures, has excellent flexibility, and also has better light transmittance, transmittance, flame retardancy, and low refractive index. Summary of the invention
[0008] The main purpose of the present invention is to provide an OCA optical film and a preparation method thereof. The OCA optical film has excellent aging and yellowing resistance, high temperature resistance, and flexibility, and also has better light transmittance, transmittance, flame retardancy, and low refractive index.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] On one hand, the present invention provides an OCA optical film, comprising a five-layer structure, which is, in sequence, a fluorine-containing profiled film layer, a silicon-containing adhesive layer, a modified PET matrix, a silicon-containing adhesive layer and a fluorine-containing profiled film layer; the raw material for preparing the silicon-containing adhesive layer is a silicon-containing adhesive.
[0011] Traditional OCA adhesives are mainly acrylic and polyurethane systems, but the poor heat resistance of the adhesives in this system will further cause the film material to turn yellow, limiting the application of OCA.
[0012] The OCA optical film of the present application uses a modified silicon-containing adhesive layer to bond the layers together, and the modified PET matrix is used in combination, which can further improve the light transmittance of the OCA adhesive. The reason may be that the silicon-containing adhesive layer of the present application has a high light transmittance. When the traditional PET is used, its light transmittance will be reduced due to the low light transmittance of PET, which will lead to a decrease in the overall light transmittance of the OCA film. The modified PET matrix of the present application has a higher light transmittance, and after compounding, the light transmittance of the OCA film can be maintained excellent. In addition, the OCA film of the present application has excellent aging and yellowing resistance, high temperature resistance, and flexibility.
[0013] In some embodiments, the thickness of the silicon-containing adhesive layer is 100 to 3000 μm; the thickness of the fluorine-containing special-shaped film layer is 1000 to 3000 μm.
[0014] In some embodiments, the thickness ratio of the silicon-containing adhesive layer to the modified PET substrate is 1:(0.1-10).
[0015] The present application adjusts the thickness ratio of the silicon-containing adhesive layer to the modified PET substrate, which can prevent the bonding effect from being deteriorated due to low bonding force on the one hand, and prevent more reflection and scattering of light when passing through the OCA film on the other hand, resulting in a decrease in the light transmittance of the OCA film.
[0016] In some embodiments, the silicon-containing adhesive comprises a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:(0.8-1.5); the modified inorganic silicon adhesive consists of a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I:
[0017]
[0018] wherein R1 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl;
[0019] R2 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, including one methyl, vinylmethyl, styrene or perfluorovinylmethyl;
[0020] R3 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, propenyl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, which must contain one propenyl or methacryl;
[0021] x, y, and z are each independently an integer between 1 and 100; p is an integer between 1 and 200; is the grafting site with the shell;
[0022] The structure of structural unit A is as follows
[0023] in A is a chemical bond connection site; structural unit B is a cross-linker residue.
[0024] In some embodiments, the method for preparing the silicon-containing adhesive comprises the following steps, measured in parts by weight:
[0025] S1. Prepare a suspension of product A and product B after hydrolysis and polycondensation of any two of tin tetrachloride, zirconium tetrachloride, ethyl orthosilicate and tetrabutyl titanate with water, heat to reflux, continue stirring for 2 to 3 hours, centrifuge after the reaction, wash with ethanol and dry, and calcine at 500 to 600° C. to obtain an inorganic silicon adhesive;
[0026] S2, 80-90 parts of an organosiloxane containing an R1 group, 80-90 parts of an organosiloxane containing an R2 group and 80-90 parts of an organosiloxane containing an R3 group are mixed, 170-180 parts of toluene, 45-50 parts of deionized water and 2-4 parts of concentrated sulfuric acid are added, the temperature is raised to 70-80° C. and stirred at a constant temperature for 1-2 hours, after the reaction is completed, 35-45 parts of a compound containing a structural unit A and 160-180 parts of heptane are added, the temperature is raised to 40-50° C. and the reaction is continued for 12-14 hours, after the reaction is completed, the mixture is cooled to room temperature to obtain a polysiloxane copolymer precursor;
[0027] S3, in an inert protective gas atmosphere, 60-70 parts of tetraethyl orthosilicate, 180-220 parts of the inorganic silicone adhesive in step S1, 80-90 parts of the polysiloxane copolymer precursor and the crosslinking agent in step S2 are mixed, triethylamine is added, the temperature is raised to 70-80° C., and the mixture is stirred at a constant temperature for 1-3 hours. After the reaction is completed, a modified inorganic silicone adhesive is obtained;
[0028] S4, mixing the organic silicon adhesive and the inorganic silicon adhesive in step S3 and stirring them evenly to obtain a silicon-containing adhesive.
[0029] The structure of the organic silicon adhesive is shown in Formula I:
[0030]
[0031] In some embodiments, in step S3, the cross-linking agent has any one of the following structures:
[0032] (1)
[0033] (2) wherein n is an integer of 0 to 8, and R4 is any one of -COOH, -OH, -SH or -NCO.
[0034] In some embodiments, the preparation method of the compound containing structural unit A comprises the following steps: mixing 3-amino-1-propanol and 2,6-di-tert-butyl-4-chlorophenol, adding them to N,N-dimethylformamide, adding an acid binding agent, heating to 35-45° C. and stirring at a constant temperature for 12-14 hours, filtering after the reaction is completed, and obtaining a compound containing structural unit A.
[0035] In some embodiments, the preparation method of the modified PET matrix comprises the following steps, by weight: melt blending 1 to 3 parts of ionomer, 70 to 74 parts of PET and 1 to 2 parts of chain extender, extruding through a twin-screw extruder, and cooling and cutting to form.
[0036] The OCA film of the present application is prepared by compounding a fluorine-shaped film layer, a silicon-containing adhesive layer, and a modified PET matrix, wherein the fluorine-shaped film layer and the silicon-containing adhesive layer have a high light transmittance. Although traditional PET has a certain light transmittance, there is still room for improvement.
[0037] The modified PET matrix of the present application can obtain a modified PET matrix with low transparency and refractive index by melt blending of ionomer, PET and chain extender and extrusion molding, thereby improving the transmittance of the OCA film and reducing the refractive index, and at the same time enhancing the flame retardant properties of the OCA film. The reason may be that the PET molecular chain structure is regular and has strong crystallization properties, but the rigidity of its molecular chain causes the movement ability of the molecular chain to be hindered. The homemade ionomer structure of the present application contains a small amount of ionizable groups, which can produce hydrogen bonds with the PET matrix to form physical crosslinks, thereby improving the transmittance of PET. At the same time, it can also interact with the silicon-containing adhesive layer to increase the bonding force between the modified PET matrix and the silicon-containing adhesive layer. In addition, the ionomer structure also contains a certain amount of N elements to improve the flame retardant properties of the OCA film.
[0038] In some embodiments, the method for preparing the ionomer comprises the following steps:
[0039] A1, N-methylallylamine, diglycolamine and cyanuric chloride were mixed, N, N-dimethylformamide was added, and then an acid binding agent was added, the temperature was raised to 40-45°C and stirred at a constant temperature for 14-16 hours, and after the reaction was completed, the mixture was concentrated and dried under reduced pressure to obtain compound A;
[0040] A2. Compound A, 3-methyl-1-butene and toluene are mixed, and a catalyst is added. The mixture is heated to 80-90° C. and stirred at a constant temperature for 2-3 hours. After the reaction is completed, an ionomer is obtained.
[0041] In some embodiments, in step A1, the molar ratio of N-methylallylamine, diglycolamine and cyanuric chloride is (0.9-1.1):(2-2.2):1.
[0042] In some embodiments, in step A2, the molar ratio of compound A to 3-methyl-1-butene is 1:(2-2.4).
[0043] In some embodiments, in step A2, the catalyst is benzoyl peroxide and / or ammonium persulfate.
[0044] On the other hand, the present invention provides a method for preparing an OCA optical film, comprising the following steps: applying a layer of silicon-containing adhesive on the upper and lower surfaces of a modified PET substrate to obtain a silicon-containing adhesive layer, scraping it flat and then attaching a fluorine-containing special-shaped film layer to the silicon-containing adhesive layer, and curing it at 200-300°C for 1-2 hours to obtain the OCA optical film.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The OCA optical film of the present invention is formed by bonding and compounding a fluorine-containing special-shaped film layer, a silicon-containing adhesive layer and a modified PET substrate. The OCA optical film has excellent aging and yellowing resistance, high temperature resistance, and flexibility. In addition, it has better light transmittance, transmittance, flame retardancy and low refractive index.
[0047] (2) The present invention adjusts the thickness ratio of the silicon-containing adhesive layer to the modified PET substrate, thereby preventing the bonding effect from being deteriorated due to low bonding force, and preventing more reflection and scattering of light when passing through the OCA film, which would lead to a decrease in the light transmittance of the OCA film.
[0048] (3) The self-made ionomer structure of the present invention contains a small amount of ionizable groups, which can produce hydrogen bonds with the PET matrix to form physical crosslinks, thereby improving the light transmittance of PET. At the same time, it can also interact with the silicon-containing adhesive layer to increase the bonding force between the modified PET matrix and the silicon-containing adhesive layer. In addition, the ionomer structure also contains a certain amount of N elements to improve the flame retardant properties of the OCA film.
[0049] (4) On the one hand, the silicon-containing adhesive of the present invention has a core-shell structure, which can improve the reflectivity of the adhesive and reduce the refractive efficiency through the complementary and synergistic effect of a variety of different elements; on the other hand, the outermost layer of the silicon-containing adhesive has a modified POSS structure, the double bonds in which can improve the adhesive's bonding ability, and the structure also has hindered phenol groups that improve the adhesive's anti-aging and yellowing properties. At the same time, the chemical structure of the POSS group gives the adhesive a certain toughness; on the other hand, the cross-linking agent cross-links the silicon-containing adhesive, increases its molecular weight and viscosity, and the phenyl groups therein can form π-π stacking, thereby improving the heat resistance of the adhesive. DETAILED DESCRIPTION
[0050] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] In the following preparation examples, embodiments and comparative examples, PET was purchased from Ningbo Jianxing Plastic Chemical Co., Ltd.; CESA-extend chain extender was purchased from Shenzhen Huixin Plastic Chemical Co., Ltd.; and acrylic adhesive was purchased from Juli (Dongguan) New Material Technology Co., Ltd.
[0052] Preparation Example 1
[0053] The preparation method of a compound containing structural unit A comprises the following steps: mixing 0.3 mol of 3-amino-1-propanol and 0.36 mol of 2,6-di-tert-butyl-4-chlorophenol, adding into 300 mL of N,N-dimethylformamide, adding 0.42 mol of sodium bicarbonate, heating to 40° C. and stirring at constant temperature for 13 hours, filtering after the reaction is completed, and obtaining a compound containing structural unit A.
[0054] Preparation Example 2
[0055] The silicon-containing adhesive comprises a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:1.3; the modified inorganic silicon adhesive consists of a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I:
[0056] Wherein, R1 is methyl, R2 is methyl and hydrogen, R3 is propenyl and hydroxyl; x is 40, y is 40, z is 40; p is 30; is the grafting site with the shell layer; the structure of structural unit A is as follows
[0057] in A is a chemical bond connection site; structural unit B is a cross-linker residue.
[0058] The preparation method of the silicon-containing adhesive comprises the following steps, measured by weight:
[0059] S1. Mix 100 parts of tetraethyl orthosilicate, 2L of deionized water and 70mL of 2mol / L sodium hydroxide solution, and perform hydrolysis and polycondensation at room temperature for 3h. Centrifuge to obtain product A. Prepare material A by mixing 300 parts of tetrabutyl titanate and 900 parts of ethanol. Prepare material B by mixing 900 parts of ethanol, 90 parts of deionized water and 72 parts of glacial acetic acid. Add material B to material A and stir at room temperature for 2h. Centrifuge to obtain product B. Mix product A and product B with 2.5L of deionized water to form a suspension. Heat to reflux state. Continue stirring for 2.5h. Centrifuge after the reaction. Wash with ethanol and dry. Calcined at 550°C to obtain an inorganic silicon adhesive.
[0060] S2, 85 parts of dimethyldimethoxysilane, 85 parts of methyldiethoxysilane and 85 parts of allyltriethoxysilane were mixed, 175 parts of toluene, 47 parts of deionized water and 3 parts of 98wt% concentrated sulfuric acid were added, the temperature was raised to 75°C and stirred at constant temperature for 1.5h, after the reaction was completed, 40 parts of the compound containing structural unit A and 170 parts of heptane were added, the temperature was raised to 45°C and the reaction was continued for 13h, and after the reaction was completed, the reaction was cooled to room temperature to obtain a polysiloxane copolymer precursor;
[0061] S3, in a N2 gas atmosphere, 7 parts of tetraethyl orthosilicate, 200 parts of the inorganic silicone adhesive in step S1, 85 parts of the polysiloxane copolymer precursor in step S2 and 0.2 parts of terephthalic acid methanol were mixed, 20 parts of triethylamine were added, the temperature was raised to 75°C, and the mixture was stirred at a constant temperature for 2 hours. After the reaction was completed, a modified inorganic silicone adhesive was obtained;
[0062] S4, mixing the organic silicon adhesive and the inorganic silicon adhesive in step S3 and stirring them evenly to obtain a silicon-containing adhesive.
[0063] Wherein, the compound containing structural unit A is prepared by Preparation Example 1; the structure of the organic silicon adhesive is shown in Formula II:
[0064]
[0065] Preparation Example 3
[0066] The preparation method of ionomer comprises the following steps:
[0067] A1, 0.5 mol N-methylallylamine, 1.05 mol diglycolamine and 0.5 mol cyanuric chloride were mixed, 1 L N, N-dimethylformamide was added, and then 0.7 mol sodium carbonate was added, the temperature was raised to 42°C and stirred at constant temperature for 15 hours, and after the reaction was completed, the mixture was concentrated and dried under reduced pressure to obtain compound A;
[0068] A2. Mix 0.5 mol of compound A, 1.1 mol of 3-methyl-1-butene and 1.8 L of toluene, add 0.5 g of benzoyl peroxide, raise the temperature to 85°C and stir at this temperature for 2.5 h. After the reaction is completed, an ionomer is obtained.
[0069] Preparation Example 4
[0070] The specific implementation method of the ionomer is the same as that of Preparation Example 3, except that an equal mole of (3-aminocyclobutane-1,1-diyl) dimethanol is used instead of 3-methyl-1-butene.
[0071] Preparation Example 5
[0072] The specific implementation method of the ionomer is the same as that of Preparation Example 3, except that the amount of 3-methyl-1-butene is 0.5 mol.
[0073] Preparation Example 6
[0074] The specific implementation method of the ionomer is the same as that of Preparation Example 3, except that 1,3-dichloro-2-(chloromethyl)propane is used instead of cyanuric chloride.
[0075] Preparation Example 7
[0076] The specific implementation method of the ionomer is the same as that of Preparation Example 3, except that the amount of diglycolamine is 0.5 mol.
[0077] Preparation Example 8
[0078] The preparation method of the modified PET matrix comprises the following steps, calculated by weight: melt blending 2 parts of ionomer, 72 parts of PET and 1.5 parts of CESA-extend chain extender, extruding through a twin-screw extruder, cooling and cutting to form.
[0079] Among them, the ionomer is prepared by Preparation Example 3.
[0080] Preparation Example 9
[0081] The preparation method of the modified PET matrix is the same as that of Preparation Example 8, except that the ionomer is prepared by Preparation Example 4.
[0082] Preparation Example 10
[0083] The preparation method of the modified PET matrix is the same as that of Preparation Example 8, except that the ionomer is prepared by Preparation Example 5.
[0084] Preparation Example 11
[0085] The preparation method of the modified PET matrix is the same as that of Preparation Example 8, except that the ionomer is prepared by Preparation Example 6.
[0086] Preparation Example 12
[0087] The preparation method of the modified PET matrix is the same as that of Preparation Example 8, except that the ionomer is prepared by Preparation Example 7.
[0088] Example 1
[0089] An OCA optical film comprises a five-layer structure, which comprises, from top to bottom, an FEP film layer, a silicon-containing adhesive layer, a modified PET matrix, a silicon-containing adhesive layer and an FEP film layer; the raw material for preparing the silicon-containing adhesive layer is a silicon-containing adhesive.
[0090] The preparation method of OCA optical film includes the following steps: applying a layer of 1500 μm thick silicon-containing adhesive on the upper and lower surfaces of a modified PET substrate with a thickness of 7500 μm to obtain a silicon-containing adhesive layer, and then attaching a 2000 μm FEP film layer to the silicon-containing adhesive layer after flattening, and curing it at 250° C. for 1.5 hours to obtain the OCA optical film.
[0091] Among them, the modified PET matrix is prepared by Preparation Example 8, and the silicon-containing adhesive is prepared by Preparation Example 2.
[0092] Example 2
[0093] An OCA optical film comprises a five-layer structure, which comprises, from top to bottom, an FEP film layer, a silicon-containing adhesive layer, a modified PET matrix, a silicon-containing adhesive layer and an FEP film layer; the raw material for preparing the silicon-containing adhesive layer is a silicon-containing adhesive.
[0094] The preparation method of OCA optical film comprises the following steps: applying a layer of silicon-containing adhesive with a thickness of 100 μm on the upper and lower surfaces of a modified PET substrate with a thickness of 1000 μm respectively to obtain a silicon-containing adhesive layer, and then attaching a 1000 μm FEP film layer to the silicon-containing adhesive layer after flattening, and curing it at 200° C. for 2 hours to obtain the OCA optical film.
[0095] Among them, the modified PET matrix is prepared by Preparation Example 8, and the silicon-containing adhesive is prepared by Preparation Example 2.
[0096] Example 3
[0097] An OCA optical film comprises a five-layer structure, which comprises, from top to bottom, an FEP film layer, a silicon-containing adhesive layer, a modified PET matrix, a silicon-containing adhesive layer and an FEP film layer; the raw material for preparing the silicon-containing adhesive layer is a silicon-containing adhesive.
[0098] The preparation method of OCA optical film comprises the following steps: applying a layer of silicon-containing adhesive with a thickness of 3000 μm on the upper and lower surfaces of a modified PET substrate with a thickness of 300 μm to obtain a silicon-containing adhesive layer, and then attaching a 3000 μm FEP film layer to the silicon-containing adhesive layer after flattening, and curing it at 300° C. for 1 hour to obtain the OCA optical film.
[0099] Among them, the modified PET matrix is prepared by Preparation Example 8, and the silicon-containing adhesive is prepared by Preparation Example 2.
[0100] Example 4
[0101] An OCA optical film and a preparation method thereof, the specific implementation manner is the same as Example 1, except that the modified PET matrix is prepared by Preparation Example 9.
[0102] Example 5
[0103] An OCA optical film and a preparation method thereof, the specific implementation manner is the same as Example 1, except that the modified PET matrix is prepared by Preparation Example 10.
[0104] Example 6
[0105] An OCA optical film and a preparation method thereof, the specific implementation manner is the same as Example 1, except that the modified PET matrix is prepared by Preparation Example 11.
[0106] Example 7
[0107] An OCA optical film and a preparation method thereof, the specific implementation manner is the same as Example 1, except that the modified PET matrix is prepared by Preparation Example 12.
[0108] Comparative Example 1
[0109] An OCA optical film and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that a PET matrix is used instead of a modified PET matrix.
[0110] The preparation method of the PET matrix comprises the following steps, calculated by weight: melt-blending 72 parts of PET and 1.5 parts of dicyandiamide through a double screw, extruding with a rod extruder, and cooling and cutting into shape.
[0111] Comparative Example 2
[0112] An OCA optical film and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that an acrylic adhesive is used instead of a silicon-containing adhesive.
[0113] Performance Test:
[0114] (1) Anti-ultraviolet performance: The OCA optical film was placed in a UV aging chamber, with a 1kW lamp at a distance of 50 cm, and continuously irradiated for 100 hours. The yellowing index of the adhesive layer was measured according to GB / T7975-2005 standard;
[0115] (2) Peel strength test: The peel strength of the silicon-containing adhesive layer in the optical film is tested according to GB / T7122-1996 "Determination of peel strength of high-strength adhesives - Floating roller method";
[0116] (3) Elongation test: The OCA optical film is cut into dumbbell shapes and tested using a tensile testing machine at a rate of 50 mm / min. The greater the elongation, the better the toughness.
[0117] (4) Temperature resistance: The OCA optical film in method (3) was placed in a 300°C environment for 3 days and the elongation was tested again;
[0118] (5) Light transmittance test: measured using a photoelectric haze meter model NDH2000;
[0119] (6) Transmittance test: measured by spectrophotometer UV3100, wavelength range 400~700nm;
[0120] (7) Flame retardant performance test: tested according to UL-94.
[0121] The adhesives of the embodiments and comparative examples were tested according to the above test method, and the results are shown in Table 1.
[0122] Table 1
[0123]
[0124]
[0125] According to the above results, it is found that the OCA optical films of Examples 1 to 3 have good anti-aging and yellowing performance, flexibility, high temperature resistance, good light transmittance, high bonding strength between layers, and good flame retardancy; Example 4 uses equimolar (3-aminocyclobutane-1,1-diyl) dimethanol to replace 3-methyl-1-butene, which leads to a decrease in the flexibility of the OCA optical film, but the increase in ionic bonds therein increases the peel strength and light transmittance of the OCA optical film; Example 5 changes the molar ratio of compound A to 3-methyl-1-butene, resulting in a slight decrease in the light transmittance and transmittance of the OCA optical film; Example 6 uses 1,3-dichloro-2-(chloromethyl)propane replaced cyanuric chloride, resulting in a decrease in the flame retardant properties of the OCA optical film; Example 7 changed the molar ratio of N-methylallylamine, diglycolamine and cyanuric chloride, resulting in a decrease in the light transmittance, transmittance and peel force of the OCA optical film; Comparative Example 1 used a PET layer instead of a modified PET matrix, resulting in a decrease in the peel force between the base layers of the OCA optical film, and at the same time, its light transmittance, transmittance and flame retardant properties decreased; Comparative Example 2 used a sub-gram adhesive layer instead of a silicon-containing adhesive layer, resulting in a decrease in the light transmittance, transmittance, anti-aging and yellowing performance, high temperature resistance and flexibility of the OCA optical film.
[0126] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. An OCA optical film, characterized in that: The invention comprises a five-layer structure, which is a fluorine-containing special-shaped film layer, a silicon-containing adhesive layer, a modified PET matrix, a silicon-containing adhesive layer and a fluorine-containing special-shaped film layer in sequence; the raw material for preparing the silicon-containing adhesive layer is a silicon-containing adhesive.
2. The OCA optical film according to claim 1, characterized in that: The thickness of the silicon-containing adhesive layer is 100 to 3000 μm; the thickness of the fluorine-containing special-shaped film layer is 1000 to 3000 μm.
3. The OCA optical film according to claim 1, characterized in that: The ratio of the thickness of the silicon-containing adhesive layer to the thickness of the modified PET substrate is 1:(0.1-10).
4. The OCA optical film according to claim 1, characterized in that: The silicon-containing adhesive comprises a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:(0.8-1.5); the modified inorganic silicon adhesive consists of a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I: wherein R1 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl; R2 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, including one methyl, vinylmethyl, styrene or perfluorovinylmethyl; R3 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, propenyl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, which must contain one propenyl or methacryl; x, y, and z are each independently an integer between 1 and 100; p is an integer between 1 and 200; is the grafting site with the shell; The structure of structural unit A is as follows in A is a chemical bond connection site; structural unit B is a cross-linker residue.
5. The OCA optical film according to claim 1, characterized in that: The preparation method of the modified PET matrix comprises the following steps, calculated by weight: melt-blending 1 to 3 parts of ionomer, 70 to 74 parts of PET and 1 to 2 parts of chain extender, extruding through a twin-screw extruder, and cooling and cutting to form.
6. The OCA optical film according to claim 5, characterized in that: The preparation method of the ionomer comprises the following steps: A1, N-methylallylamine, diglycolamine and cyanuric chloride were mixed, N, N-dimethylformamide was added, and then an acid binding agent was added, the temperature was raised to 40-45°C and stirred at a constant temperature for 14-16 hours, and after the reaction was completed, the mixture was concentrated and dried under reduced pressure to obtain compound A; A2. Compound A, 3-methyl-1-butene and toluene are mixed, and a catalyst is added. The mixture is heated to 80-90° C. and stirred at a constant temperature for 2-3 hours. After the reaction is completed, an ionomer is obtained.
7. The OCA optical film according to claim 6, characterized in that: In step A1, the molar ratio of N-methylallylamine, diglycolamine and cyanuric chloride is (0.9-1.1):(2-2.2):
1.
8. The OCA optical film according to claim 6, characterized in that: In step A2, the molar ratio of compound A to 3-methyl-1-butene is 1:(2-2.4).
9. The OCA optical film according to claim 6, characterized in that: In step A2, the catalyst is benzoyl peroxide and / or ammonium persulfate.
10. A method for preparing an OCA optical film according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: applying a layer of silicon-containing adhesive on the upper and lower surfaces of a modified PET substrate to obtain a silicon-containing adhesive layer, flattening the layer and attaching a fluorine-containing special-shaped film layer to the silicon-containing adhesive layer, curing the film at 200-300°C for 1-2 hours, and obtaining an OCA optical film.
Citation Information
Patent Citations
An OCA optical adhesive and an OCA optical adhesive film
CN107353854B
OCA adhesive, OCA layer, OCA film and application
CN116200140A
PET (Polyethylene Terephthalate) sulfonate ionomer nucleating agent and preparation method as well as application thereof
CN102911471A
POSS / PA6 (polyhedral oligomeric silsesquioxane / polycaprolactam) composite material and preparation method thereof
CN102977592A
Low-odor, low-volatile and scratch-resistant polypropylene composite material for automotive interiors and preparation method for composite material
CN105647021A